2014
DOI: 10.1902/jop.2013.130155
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Parathyroid Hormone Administration Improves Periodontal Healing in Rats

Abstract: Within the limits of the present study, intermittent administration of hPTH 1-34 led to an enhanced periodontal healing process compared with non-treated animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 51 publications
5
35
1
Order By: Relevance
“…The cementogenesis- and differentiation-related biomarkers BSP, OCN, COL1 and Osx were also stimulated by intermittent PTH. Previous in vivo studies showed that PTH administration increased cementum width in an osteoporotic rabbit model or improved the formation of newly formed cementum-like tissue in a rat model [18, 19]. Therefore, these findings together suggest that intermittent PTH can be a potential therapeutic agent for root resorption.…”
Section: Discussionmentioning
confidence: 76%
“…The cementogenesis- and differentiation-related biomarkers BSP, OCN, COL1 and Osx were also stimulated by intermittent PTH. Previous in vivo studies showed that PTH administration increased cementum width in an osteoporotic rabbit model or improved the formation of newly formed cementum-like tissue in a rat model [18, 19]. Therefore, these findings together suggest that intermittent PTH can be a potential therapeutic agent for root resorption.…”
Section: Discussionmentioning
confidence: 76%
“…Micro‐CT and histological observations demonstrated that the systemic intermittent PTH improved bone formation in periodontal defects at 2 weeks and 4 weeks postoperative. Previously, it was shown that intermittent PTH treatment improved alveolar bone levels affected by periodontitis in rats and humans (Barros et al, ; Bashutski et al, ; Marques et al, ; Vasconcelos et al, ). The cyclic adenosine monophosphate (cAMP)–protein kinase signalling pathway response to PTH 1 receptor (PTH1R) activation is considered to be the main mechanism that mediates the anabolic action of PTH in bone (Swarthout, D’Alonzo, Selvamurugan, & Partridge, ; Yang, Guo, Divieti, & Bringhurst, ).…”
Section: Discussionmentioning
confidence: 98%
“…The administration of PTH was performed essentially as described by Vasconcelos et al (). Animals in the PTH group received intermittent subcutaneous injections of recombinant human PTH (1–34) (Sigma‐Aldrich) at 40 µg/kg every 2 days for 2 weeks or 4 weeks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…, Vasconcelos et al. ) and human (Bashutski et al. ) experiments have shown that intermittent administration of PTH or its recombinant form – teriparatide – results in less alveolar bone loss, a reduced number of inflammatory cells in the inflamed gingival area, and improved bone healing.…”
mentioning
confidence: 99%